The tragedy of errors : women contribution to poverty alleviation and their security under environmentally stressed conditions - Datta, Dilip Kumar, Dr.; Forum on Women in Security and International Affairs (Bangladesh); Bangladesh Freedom Foundation (Dhaka : Forum on Women in Security and International Affairs : Bangladesh Freedom Foundation, 2005)
Study with reference to some coastal, waterlogged regions of Khulna and Jessore districts of Bangladesh.
Includes bibliographical references (p. [115]-116).
Keywords: Women in development -- Bangladesh -- Khulna District; Women in development -- Bangladesh -- Jessore District; Women and the environment -- Bangladesh -- Khulna District; Women and the environment -- Bangladesh -- Jessore District